1996
DOI: 10.1165/ajrcmb.15.6.8969267
|View full text |Cite
|
Sign up to set email alerts
|

Protection of human nasal respiratory epithelium from complement-mediated lysis by cell-membrane regulators of complement activation.

Abstract: Complement in the respiratory tract protects the host from invading micoorganisms and other inhaled insults, but may damage normal tissue. Recently we reported that human respiratory epithelium from the nose to the alveoli expresses three cell-membrane regulators of complement activation: membrane cofactor protein (MCP, CD46), decay accelerating factor (DAF; CD55), and CD59. In this study we investigated whether two of these complement-regulatory proteins, DAF and CD59, protect human nasal epithelial cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…These cell membrane CIP molecules are expressed in healthy subjects and their expression is increased in various lung diseases characterised by inflammation or malignant transformation12 and also in human lung cancer cell lines, both unstimulated and stimulated with proinflammatory cytokines 1314 We also found that these molecules are essential for protecting cultured human nasal respiratory epithelial cells from being lysed by human serum complement 15…”
mentioning
confidence: 79%
“…These cell membrane CIP molecules are expressed in healthy subjects and their expression is increased in various lung diseases characterised by inflammation or malignant transformation12 and also in human lung cancer cell lines, both unstimulated and stimulated with proinflammatory cytokines 1314 We also found that these molecules are essential for protecting cultured human nasal respiratory epithelial cells from being lysed by human serum complement 15…”
mentioning
confidence: 79%
“…Additionally, lung tumors show minimal deposition of C3b and no activation of the lytic membrane attack complex. In vitro studies have confirmed that lung cancer cell lines are extremely resistant to complement-mediated lysis, and this resistance is much higher than that observed in normal cells such as human nasal epithelium primary cell cultures (5,39). Besides, lung cancer cell lines have the ability of limiting the activation of complement in their cell membrane and express high levels of cell membrane complement inhibitory proteins (5).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it was suggested that membrane-associated complement regulatory proteins may act as mediators of lung cancer resistance to complement activation (38). However, neutralizing antibodies against CD46 and CD59 are not effective in increasing the susceptibility to complementmediated lysis (5), whereas the same antibodies are very effective in facilitating complement-mediated lysis of noncancer nasal epithelial cells (39). This suggests the existence of alternative mechanisms that would explain the resistance to complement activation in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…C3aR, expressed in healthy epithelial cells, submucosal glands, and nerves, is additionally expressed in the endothelium of surrounding sinuses and muscle layers in severe, persistent AR [21]. The nasal and respiratory tract epithelia express complement regulatory molecules such as membrane cofactor protein (CD46), decay-accelerating factor (DAF, CD55), and CD59 [22,23], suggesting complement activation is tightly controlled in the nasal mucosa. However, it is not known if or how such cellular complement regulators are modulated during allergy.…”
Section: Complement Activation In Allergic Airway Diseasesmentioning
confidence: 99%